Simplified approach for evaluating land suitability and potential climate change impacts for feedstocks production and developing supplemental irrigation need in Ethiopia - CGIAR Research Program on Climate Change, Agriculture and Food Security (2018)
In order to establish the scientific evidence base the researchers have put together a paper on ‘Evaluating land suitability and potential climate change impacts on Alfalfa (Medicago sativa) production in Ethiopia’ and submitted for publication in peer reviewed journal (Climate and Development) for publication (https://www.tandfonline.com/loi/tcld20)